Da filantropia à responsabilidade social - Assis, Karina Gomes de (2010)
In this work, from a case study approach, we discuss social responsibility from the idea of philanthropy. Analyzing the Brazilian subsidiary of a north-american cosmetics company whose disclosures says their social actions began in the nineteenth century, we point out and discuss the changes in the forms of involvement with society and how it deals with the issue of social responsibility. We addressed the most significant changes the behavior of the company in social issues and the kind of engagement with actors outside the firm. Therefore, we performed the analysis of the material of the company and its social projects, interviews with people involved in these projects and a literature search on the topics addressed. The results show a change in the treatment of social issues by the company and the importance of emotion in marketing the company and its social responsibility programs for customers and resellers of the brand, while for the market the use of this emotion is justified in a ' more rational ' manner. It became apparent even to the insertion of new actors in the framework of responsibility and commitment: government agencies, resellers, customers, non-governmental organizations are being included in the context of responsibility, making the idea of social responsibility be seen as a joint and not an individual attitude of the company.